Endovascular management of hepatic artery pseudoaneurysm - R., Marlina Tanty; H., Hilwati; M., A. Sobri (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Hepatic artery pseudoaneurysms (HAP) is a result of injury to the hepatic artery and must be treated due to its high risk of rupture. Endovascular treatment of pseudoaneurysm is effective and minimally invasive. We describe four cases of HAPs that presented with gastrointestinal (GI) bleed. The HAPs developed as a consequence of surgery for carcinoma, infection, trauma due to motor-vehicle accident and biliary instrumentation. Diagnoses were made using CT and conventional angiography. Embolisations were done either to the pseudoaneurysm or the parent artery using glue, Onyx or coils via microcatheter systems. Postembolisation runs showed no opacification of the pseudoaneurysms and the GI bleed resolved with no recurrence. The final outcome differs according to each patient’s underlying illness. We highlight our experience in the endovascular management of HAP using various embolic agents and in particular, Onyx. To the best of our knowledge, this is the first reported case of Onyx embolization of HAP.